2014
DOI: 10.1021/la503089k
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of the Wettability of Multilayer Graphene Using Highly Ordered Pyrolytic Graphite as a Model Material

Abstract: We report the intrinsic water contact angle (WCA) of multilayer graphene, explore different methods of cleaning multilayer graphene, and evaluate the efficiency of those methods on the basis of spectroscopic analysis. Highly ordered pyrolytic graphite (HOPG) was used as a model material system to study the wettability of the multilayer graphene surface by WCA measurements. A WCA value of 45° ± 3° was measured for a clean HOPG surface, which can serve as the intrinsic WCA for multilayer graphene. A 1 min plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
84
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 47 publications
14
84
1
Order By: Relevance
“…This result is in line with other studies that have shown graphite surfaces to be mildly hydrophilic with a contact angle of about 50ᵒ, 35,36,37 Although higher aqueous contact angle values have been reported in the literature, 38,39,40 variations are expected depending on the sample quality, measurement environment (including surface contamination which increases the contact angle) and droplet size. 35,36,41 Given the short timescale (<5 s) on which the droplet was deposited after cleavage of surface, 9 the value we report can be taken as the intrinsic CA of 1 mM NaClO4 at AM HOPG, and is in line with theoretical predictions. 11 % at +1.13 V, while the CA was reduced from 51ᵒ to 38ᵒ.…”
Section: Voltage Effect On Electrowettingsupporting
confidence: 91%
“…This result is in line with other studies that have shown graphite surfaces to be mildly hydrophilic with a contact angle of about 50ᵒ, 35,36,37 Although higher aqueous contact angle values have been reported in the literature, 38,39,40 variations are expected depending on the sample quality, measurement environment (including surface contamination which increases the contact angle) and droplet size. 35,36,41 Given the short timescale (<5 s) on which the droplet was deposited after cleavage of surface, 9 the value we report can be taken as the intrinsic CA of 1 mM NaClO4 at AM HOPG, and is in line with theoretical predictions. 11 % at +1.13 V, while the CA was reduced from 51ᵒ to 38ᵒ.…”
Section: Voltage Effect On Electrowettingsupporting
confidence: 91%
“…53-65° and it adsorbs airborne hydrocarbons in the ambient air to minimize surface energy, i.e., appear more hydrophobic. 76,230,241 Similar results were also reported for monolayer graphene on copper and multilayer graphene on nickel 75,77 and the surface energy and wettability of freshly synthesized graphene on copper was found to be dependent upon exposure time to ambient air. 75 Lai et al attributed the change in graphene wettability to adsorption of both water molecules and hydrocarbons 63 and Nioradze et al demonstrated that HOPG electroactivity is significantly affected by organic impurities in water and air.…”
Section: Discussionsupporting
confidence: 78%
“…230 PG has a bubbly surface -corroborating Raman and XRD data that this sample is turbostratic with poor ABAB layer stacking -and step edges are not clearly defined. …”
Section: Step Edge Densitymentioning
confidence: 62%
See 2 more Smart Citations